The Effect Of Aloe Vera And Manuka Honey On IL-1 Level In Periodontitis Rats - Muchaeroni, Isa Anshori; Praptiningsih, Rahmawati Sri; Feranisa, Anggun Feranisa; Aziz, Brahmadhia Satrio (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Periodontitis is a chronic inflammatory disease that occurs as a result of the immune system's response to bacterial infection of the gums and surrounding tissues. This condition is caused by chronic inflammation and increased levels of proinflammatory mediators associated with chronic infectious conditions. Periodontitis can trigger inflammation by increasing the level of interleukin-1 (IL-1), which plays a role in the inflammatory response. Aloe vera (Aloe vera) and manuka honey are known to have anti-inflammatory properties and inhibits the production of pro-inflammatory cytokines, including IL-1. Purpose of this research to determine the effect of Aloe Vera and Manuka Honey on IL-1 level in periodontitis rats..Method: 30 rats were randomly divided into four groups; control group, Aloe vera groups, Madu manuka group, combination of Aloe Vera and Manuka Honey group. Aloe vera and Manuka Honey were injected at doses 150 uL in the gingival. At the 5th day after treatment, all rats were terminated and Elisa from gingival tissue was performed to identify the level of IL-1.Result: The results a significant decrease of IL-1 in combination of manuka honey and Aloe Vera group(p<0.000) compared to control groupConclusion: The combination of Aloe Vera and manuka honey significantly decreased on IL-1 level.